PBwiki on-line learning: The effectiveness of pedagogical role online teachers' on students with difference learning style in their critical thinking - Rathakrishnan, A Mohan (2016)
PBwiki (Peanut Butter wiki) is an asynchronous online learning that integrates collaborative learning.By using this web-based software tool, students can create, add, remove and edit content in hypertext quickly and easily.In this paper, a study on the teachers’ pedagogical roles on students’ critical thinking skill in a PBwiki environment will be discussed.The students’ learning style (active or reflective learning style) as a moderating variable was investigated to identify whether PBwiki online learning influence their critical thinking in essay writing.A total of 120 Form Six (Grade 12) students from two high schools in Penang were involved in this 2x2 factorial quasi-experimental study.These students have to write and edit their essays in General Study’s subject with the assistance of pedagogical role online teachers (PROT).Felder and Soloman (2001) instrument were used to measure the moderating variable.Paul’s (1993) model were used to analyze student’s critical thinking in online General Studies essay writing.The findings shows that students who received the PROT treatment performed significantly better in critical thinking score and enhanced students’ critical thinking in General Studies essay writing